Kajian Penempatan Recloser Pada Jaringan Distribusi Menggunakan Metode Algoritma Genetika Berdasarkan Keandalan Maksimum - Syahru Ramadhan Indra; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The distribution system is an important part of the electrical energy distribution activities as directly connected to the customers. Therefore, the distribution system is always required to have good reliability. One way to increase reliability is using recloser. Optimal placement of recloser will be able to maximize reliability. The author used a genetic algorithm method in determining the optimal position of recloser. Objective function is combining SAIFI and SAIDI. SAIFI and SAIDI are calculated using section technique method. Simulation calculations using MATLAB (Matrix Laboratory) programming. Testing program conducted on radial distribution network. The result is recloser position within 0.157 km from existing recloser. Reduction of SAIFI after the addition of recloser is 13.23%. While the reduction of SAIDI is 2.57%.Keywords : reliability, genetic algorithm, recloser